A brief review of artificial intelligence robotic in food industry - Liaw, Siau Hwa; Lee, Te Chuan (2024)
Artificial Intelligent Robotic (AI Robotic) is the formal term for an ‘intelligent induced’ robot that can operate with vision (eye) to detect a product defect, or a control operating system to assist robot to differentiate good and reject product during production. A number of cutting-edge manufacturing automation technologies have been developed, including automatic inspection, autonomous robots, additive manufacturing, ubiquitous manufacturing, cloud manufacturing, and cyber-physical systems. Intelligent and automation technologies for worker assistance have been considered feasible. As knowledge-driven industries develop in terms of artificial intelligence and robotic automation, and to upgrade the existing and next generation of workforce, higher and further education is needed to advance a better understanding of robotic automation in manufacturers who face endless challenges such as labor shortages, high turnover labor force, product innovation, quality matters, and many others. This paper provides a general view of food supply chain challenges when faced with labor issue, environmental disaster and production problems. AI Robotic application would be a good source of problem solving in food manufacturing, food processing and food handling process